An international perspective on performance-based specifications for concrete durability, with a suggested framework for implementation - Mosoy, Florah (Department of Civil Engineering, 2025)
Reinforced concrete (RC) is one of the world's most durable building materials. However, outdated and insufficient durability specifications often lead to the early deterioration of RC structures, escalating global maintenance costs. Prescriptive durability specifications for reinforced concrete (RC) often include mix design parameters such as minimum cement content and maximum water/binder ratio, which are intended to contribute to durability. However, achieving a specific compressive strength alone does not guarantee durability. These rigid regulations stifle innovation in design and construction and often fail to capture the durability characteristics of modern concrete. Even if a mixed design complies with specifications, it may not achieve its intended service life under varying exposure conditions. This study establishes an international perspective on using performance-based specifications for concrete durability, contrasting them with the commonly used prescriptive based specifications. Performance-based approaches allow for customizing concrete mixtures to meet specific performance goals by focusing on measurable properties that ensure performance under particular conditions. These requirements can be applied to various stages, including design, service life modelling, specification, pre-qualification, and conformance evaluation. The study involved a review of current durability provisions in selected standards from the USA, Canada, Australia, Europe, India and South Africa, followed by an analysis of performance-based specifications implementation in these countries. Key factors influencing the adoption of performance-based specifications, such as regulatory frameworks, industry practices, and environmental exposure classification systems, were examined. The study proposes a practical framework for adopting performance-based specifications for concrete durability, covering aspects such as verifying environmental exposure conditions, concrete cover requirements, material constituents, alternative cementitious materials, testing methods for performance specification and also regulatory framework. This framework aims to educate professionals on the practical implications of performance-based specifications and promote its adoption for enhancing the durability and sustainability of concrete structures. By addressing these elements, this study provides a framework to establish a structured, adaptable approach that ensures concrete structures meet desired durability and service life requirements under specific environmental conditions. This framework prioritizes measurable performance criteria over rigid prescriptive measures, enabling tailored concrete mix designs that address exposure conditions, material quality, and maintenance expectations. By doing so, the proposed framework promotes innovation, sustainability, and cost-effectiveness in concrete construction, ultimately enhancing structural resilience and reducing long-term repair and maintenance costs.